Strategies for Hotel Management and Operations - Patnaik , Sudhansu (International Journal of Psychosocial Rehabilitation, 2019)
The history of management contracts in the hotel industry has been well documented, but the changing trends and alternative options have been less well covered. There is an evolution going on which is slowly but surely changing the balance of risk in favor of the owner of a hotel, and putting a greater onus on operators to ‘perform’ as custodians and managers of the investment. This paper examines contract options and structures with hotel management companies and highlights some of the trends and issues that have to be taken into consideration when choosing an operating partner. Following the turmoil in the hospitality industry in the last two years, the activities have been renewed, and developers in most sectors in both the United Kingdom and many other international and resort markets are now showing renewed optimism and interest. At the same time, there are some new companies that are prepared to make flexible and innovative agreements and to tailor the contracts directly to the needs of owners, but who has not the same "muscle" as the main hotel groups until they have brand presence.